Total exposure duration and proximity of cessation of cannabis use predict severity of sub-clinical psychotic symptoms among former users - Baskak, Bora (Psychiatry Res, 2012)
In a non-clinical military enrolment setting, former cannabis users (N=81), compared to substance-naïve controls (N=132), endorsed markedly elevated rates of schizotypy subscale scores on the Schizotypal Personality Questionnaire (SPQ). Total duration of exposure and proximity of cessation of cannabis use also had an important impact on the severity of psychosis-like symptoms.